2017
DOI: 10.1016/j.yebeh.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgical side and site on psychological symptoms following epilepsy surgery in adults

Abstract: This retrospective study examined the potential role of side and site of surgery in psychological symptom change after epilepsy surgery and determined the base rate of psychological change at the individual level. Two-hundred twenty-eight adults completed the Personality Assessment Inventory (PAI) before and after temporal (TLR; n=190) or frontal lobe resection (FLR; n=38). Repeated measures ANOVAs with bootstrapping examined differences in psychological outcome as a function of surgical site separately in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Existing results point toward improved quality of life after FLR and also lower scores on depression scales and reduced apathy [17][18][19]. Stability in psychological symptoms measured by personality assessment questionnaires is another finding [20].…”
Section: Introductionmentioning
confidence: 96%
“…Existing results point toward improved quality of life after FLR and also lower scores on depression scales and reduced apathy [17][18][19]. Stability in psychological symptoms measured by personality assessment questionnaires is another finding [20].…”
Section: Introductionmentioning
confidence: 96%
“…Besides, it is also important to report any change in the number of AEDs prescribed to the patients after surgery. Prayson and colleagues [29] demonstrated that the quantity of AEDs was reduced in only 28% of the patients after surgery, whereas 58% of the patients continued with the same AEDs after surgery. It is evidenced by the literature that the non-control of epileptic seizures directly impacts the patient’s quality of life; thus, the higher the frequency/intensity of the seizures, the more prevalent are the desadaptive emotional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, surgical laterality and location can be predisposing factors for psychological outcomes in epileptic patients post-surgery. Prayson et al [29] elucidated more significant depression and anxiety symptoms among patients with left TLE before surgery as compared to the patients with left frontal lobe epilepsy. On the other hand, Devinsky et al [36] demonstrated no association between the presence or absence of depression and anxiety and the lateralization or localization of the seizure onset before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is also important to report any change in the number of AEDs prescribed to the patients after surgery. Prayson and colleagues demonstrated that the quantity of AEDs was reduced in only 28% of the patients after surgery, whereas 58% of patients continued with the same AEDs after surgery [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, surgical laterality and location can be predisposing factors for psychological outcomes in epileptic patients post-surgery. Prayson et al [28] elucidated more significant depression and anxiety symptoms among patients with left temporal lobe epilepsy before surgery as compared to the patients with left frontal lobe epilepsy. On the other hand, Devinsky et al [33] demonstrated no association between the presence or absence of depression and anxiety and the lateralization or localization of the seizure onset before surgery.…”
Section: Discussionmentioning
confidence: 99%